Determinación del cumplimiento de las obligaciones tributarias en la empresa de la señora Dana Marieta Garcia Macanchi, de la ciudad de Yantzaza, periodo 2023 - Conza Armijos, Yorvin Paul (2025)
The curricular integration project entitled "Determination of compliance with tax obligations in the company owned by Mrs. Dana Marieta Garcia Macanchi, in the city of Yantzaza, Fiscal Year 2023" aims at verifying whether the company complies appropriately with its tax obligations when filing tax returns and making payments. To carry out this study, three fundamental objectives were established: to identify the tax obligations the company must fulfill according to current regulations, to assess the level of compliance with these obligations during the analyzed period, and to prepare a detailed report based on the findings. The methodology involved reviewing applicable tax regulations and analyzing accounting documents and tax returns, including the review of purchase and sales records, Value Added Tax (VAT) returns, Withholding Tax returns, Income Tax returns, and the Simplified Transactional Annex. Upon analyzing the collected information, discrepancies were found between the accounting records and the declared values, revealing certain irregularities in tax compliance. To facilitate the interpretation of these findings, comparative tables were created to visualize the identified differences and assess the accuracy of the company’s tax procedures. Finally, a report on the company’s compliance with tax obligations was prepared, presenting conclusions and proposals for improvement based on the findings. The report analyzed the effectiveness of the company’s tax processes and identified potential inconsistencies, leading to recommendations to strengthen internal controls to minimize errors in tax filings. Additionally, the importance of communicating these results to the owner-manager was emphasized to optimize transaction records and promote a responsible tax culture, ensuring compliance with current regulations and contributing to the country's economic development.